A three decade assessment of climate‐associated changes in forest composition across the north‐eastern USA. Issue 6 (29th April 2017) - Bose, Arun K.; Weiskittel, Aaron; Wagner, Robert G.
Summary: Climate‐associated changes in forest composition have been widely reported, particularly where changes in abiotic conditions have resulted in high mortality of sensitive species and have disproportionately favoured certain species better adapted to these newer conditions. In the north‐eastern USA and south‐eastern Canada, few studies have examined climate‐related influences associated with forest composition, and none have considered broad‐scale changes over a long temporal (>25 years) period. We used US Forest Service Forest Inventory and Analysis data from 1983 to 2014 across four north‐eastern states (Maine, New Hampshire, New York and Vermont) to assess temporal and spatial changes in the occurrence and abundance of American beech Fagus grandifolia Ehrh, sugar maple Acer saccharum L., red maple Acer rubrum L. and birch Betula spp. saplings. We also tested the effects of biotic and abiotic factors on the distribution of the four studied deciduous species over the entire period examined. Occurrence and abundance of American beech have increased substantially over the past three decades, whereas the occurrence and abundance of three other deciduous species have decreased in all ecological provinces of the north‐eastern USA, except the Midwest Broadleaf ecological province. Consequently, a clear shift in species composition is currently underway in the beech‐maple‐birch (BMB) forests of the north‐eastern USA, with uncertain consequences for future ecosystem structure and function. In the studied region and over the entire period examined, the distribution of increased occurrence and abundance of beech relative to the three other deciduous species were associated with higher temperature and precipitation as well as higher conspecific basal area and dead tree basal area. Synthesis and applications . The change from beech‐maple‐birch forests to more beech‐dominated forests with beech encroachment to new forest areas across the north‐eastern USA may continue if higher intensity harvesting and disturbances (i.e. large‐scale canopy openings) do not occur. This would be a significant management concern as beech is associated with a widespread bark disease, is commercially less desirable, and can limit natural regeneration from other species. Our results emphasize the need for management strategies such as higher intensity harvesting methods, vegetation control and limiting browsing pressure to reduce beech dominance. Abstract : The change from beech‐maple‐birch forests to more beech‐dominated forests with beech encroachment to new forest areas across the north‐eastern USA may continue if higher intensity harvesting and disturbances (i.e. large‐scale canopy openings) do not occur. This would be a significant management concern as beech is associated with a widespread bark disease, is commercially less desirable, and can limit natural regeneration from other species. Our results emphasize the need for management strategies such as higher intensity harvesting methods, vegetation control and limiting browsing pressure to reduce beech dominance.